Hachiko : a dog's story (2008)
"This heartwarming film is an American adaptation of a famous Japanese tale about a loyal Akita dog named Hachiko. This special dog, nicknamed 'Hachi,' accompanies his master Parker, a university professor, to the train station every morning to see him off and then returns to the station each afternoon to greet him at the end of his day. The emotionally complex nature of what unfolds when their uncomplicated routine becomes uninterrupted is what makes Hachi's story a tale for the ages; a dog's faithful devotion to his master exposes the great power of love and how this simplest of acts can become the grand gesture of all"--Copyright descriptive material.
Sources used: videodisc container; Copyright catalog online; Copyright description.
Richard Gere, Joan Allen, Cary-Hiroyuki Tagawa.
Keywords: Feature films; Fiction films